Process Intensification of Glucose Hydrogenation Through Excess Hydrogen Feed and Hydrogen Recycle Integration for High Purity Sorbitol Production - Yudha Dwipati Martela; Nasywa Naila Putri; Nazmi Eka Putri; Evelyne Alfi Aidina; Rieska Febrianti Amanda Putri; Nasywa Ega Agtaputri Anindya (Journal of Chemical Engineering Research Progress, 2025)
High-purity sorbitol is an essential intermediate for food, pharmaceutical, and specialty chemical applications. However, conventional glucose hydrogenation flowsheets often face challenges such as low hydrogen utilization and inadequate product purity. This study introduces a process intensification strategy at the flowsheet level, evaluated using simulation software, which combines excess hydrogen feeding with flash-based hydrogen recovery and a recycle purge loop. The approach enhances both the conversion driving force and downstream separation efficiency. Starting from a once-through base case, the intensified configuration increases the H₂-to-glucose molar feed ratio to 4:1 and incorporates mixers, splitters, and a flash separator to recover unreacted hydrogen for recycle, minimizing hydrogen loss and stabilizing reactor hydrogen availability. Simulation results indicate a significant improvement in product quality, raising sorbitol purity from 74 wt% in the base case to 99.37 wt% in the intensified scheme. Overall, the proposed excess-hydrogen-plus-recycle integration offers a scalable solution for achieving >99 wt% sorbitol while optimizing hydrogen management through an improved separation recycle sequence. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).